PENGORGANISASIAN LEMBAGA ZAKAT INFAQ SHODAQOH MUHAMMADIYAH (LAZISMU) KOTA MADIUN DALAM PEMENUHAN KEBUTUHAN WARGA TERDAMPAK BENCANA DI CIANJUR JAWA BARAT TAHUN 2022 - M. Mochtar Mas’od; Muhammad Rifa’at Adiakarti Farid; Nur Andriyani (Yayasan Nusantara Hasana Berdikari, 2024)
This research aims to identify the organizational strategies implemented by the Madiun City Zakat Infaq Shodaqoh Muhammadiyah (LazisMu) Institution in an effort to meet the needs of residents affected by the disaster in Cianjur, West Java in 2022. Optimal organization in the work environment is not only managing human resources, but also optimize existing resources, creating significant behavioral and social change. The research method used is descriptive qualitative. The research results highlight the initiatives and discretionary policies taken by LazisMu management in carrying out organizing, especially in achieving the needs of disaster-affected residents in Cianjur, West Java in 2022. The findings of this research explain the existence of five key sub-dimensions, which include alignment, governance, and governance. governance and compliance, process improvement and improvement, risk management and information technology.